Metric Dimension dan Non-Isolated Resolving Number pada Beberapa Graf - Wahyu Nikmatus Sholihah; Dafik Dafik; Kusbudiono Kusbudiono (jcgant, 2021)
Let G=(V, E) be a set of ordered set W={W_1,W_2, W_3,...,W_k} from the set of vertices in connected graph G. The metric dimension is the minimum cardinality of the resolving set on G. The representation of v on W is k set. Vector r(v|W)=(d(v, W_1), d(v, W_2), ..., d(v, W_k)) where d(x, y) is the distance between the vertices x and y. This study aims to determine the value of the metric dimensions and dimension of non-isolated resolving set on the wheel graph (W_n). Results of this study shows that for n ≥ 7, the value of the metric dimension and non-isolated resolving set wheel graph (W_n) is dim(W_n)=n-12 floor and nr(W_n)=n+12 floor. The first step is to determine the cardinality vertices and edges on the wheel graph, then determine W, with W is the resolving set G if vertices G has a different representation. Next determine non-isolated resolving set, where W on the wheel graph must have different representations of W and all x elements W is connected in W.